Synthesis, Characterization, and Micellar Behavior of Amphiphilic Chitosan Bearing Sulfate and Anisaldehyde Imine Groups - Herayati Herayati; Deana Wahyuningrum; Damar Nurwahyu Bima; Indah Puspita Sari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Amphiphilic chitosan derivatives bearing sulfate and anisaldehyde imine (anisimine) groups were successfully synthesized and characterized for potential applications as functional biomaterials. The synthesis involved two key steps: (1) sulfation of chitosan using chlorosulfonic acid to introduce O-sulfate groups, and (2) Schiff base formation via reaction with p-anisaldehyde to generate N-anisimine functionalities. Structural modifications were confirmed by Fourier-transform infrared (FTIR) spectroscopy, which showed characteristic absorption bands at 1250 cm-¹ and 820 cm-¹ corresponding to O=S=O stretching of sulfate, and a C=N stretch at 1640 cm-¹ indicating imine formation. Proton nuclear magnetic resonance (1H-NMR) spectra further verified the successful attachment of aromatic protons from p-anisaldehyde and the disappearance of primary amine peaks, confirming imination. The amphiphilic behavior and micelle-forming ability of the N-anisimine-O-sulfated (NAOS) chitosan were evaluated using pyrene as a hydrophobic fluorescent probe for determining the critical micelle concentration (CMC), which was found to be 0.012 mg/mL. The observed low CMC value indicates strong self-assembly capability in aqueous media. These results suggest that NAOS chitosan possesses promising structural and surface-active properties suitable for advanced applications in drug delivery and cosmetic formulations.